Estudo da dispersão pós-alimentar em larvas de moscas-varejeiras via autômatos celulares - Lima, Ernesto Augusto Bueno da Fonseca [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
In this paper, a computational analysis, using a cellular automata model, has been developed to analyze post-feeding dispersal behavior of blow y larvae. This model aimed to: simulate the exponential decline of pupal number in relation to the feed source and spatial oscillation due to larval interaction during dispersal; study whether the prior pupal presence in uences distribution patterns of larval frequency; and compare obtained unidirectional dispersal patterns to the cross-dimensional ones. The cellular automata (CA) model was able to successfully reproduce the essential features of the larval dispersal process and, thus, show the importance of local interaction in the studied dispersal process dynamics. Oscillations could be explained by the interaction among dispersing larvae and intrinsic pupation time. The box size and the initial larval density were important factors for the experiment because they in uenced the results. Results showed that the unidirectional dispersal could be used to simulate the larval dispersion that occurs in the natural environment, because both models had a similar result. These results are important to understand how di erent factors can in uence the dynamics of blow y larval dispersal, bringing important results for behavioral ecology and forensic entomology

Neste trabalho desenvolveu-se um modelo matemático utilizando o formalismo de autô- matos celulares para análise da dispersão pós-alimentar em larvas de moscas varejeiras. Os principais objetivos do modelo são: reproduzir o decréscimo exponencial do número de pupas em relação à fonte de alimento e a oscilação espacial devido à interação entre as larvas durante o processo de dispersão; investigar se a presença prévia de pupas in uencia os padrões de distribuição de freqüência larval; comparar os padrões de dispersão obtidos numa caixa retangular (unidirecional) com os de uma caixa em cruz (arena). O modelo de autômato celular (AC) foi capaz de reproduzir as características principais do processo de dispersão larval. Tal sucesso revela a importância da interação local na dinâmica do processo estudado. As oscilações se devem a combinação de diferentes mecanismos são eles: a interação entre as larvas que dispersam e o tempo intrínseco de pupação. O tamanho da caixa e a densidade de larvas inicial são fatores importantes para o sucesso do experimento já que in uenciam na interpretação dos resultados. Os resultados sugerem que o modelo de dispersão unidirecional pode ser usado para simular a dispersão larval que ocorre em ambiente natural (arena), pois ambos obtiveram resultados similares. Este estudo tem importância ecológica, epidemiológica e em entomologia forense
Keywords: Mosca-varejeira; Entomologia